Composição de um banco de expressões faciais brasileiro: um estudo de validação e comparação transcultural - Rodrigues, Marcelli Roberto (2015)
Facial expressions function as an extremely adaptive non-verbal form of communication. However, there is a debate regarding the universality of emotions. This study aimed to create and carry out a cross-cultural comparison of a Brazilian facial expressions database. Fifteen actors in the city of João Pessoa were instructed to pose expressions of happiness, fear, disgust, sadness, anger, surprise and the neutral face. The sample of the validation study was composed of 242 undergraduate students from João Pessoa/Brazil, Ribeirão Preto/Brazil and Barcelona/Spain. The results show a high recognition rate of expressions in different regions, getting above 80% frequency (happiness, anger, surprise and neutral faces), approximately 70% (disgust), however, below of 45% for fear. Some emotions were differently attributed between locations, but overall there was agreement in the evaluation of judges. The high recognition rates are evidence in favor of the universality hypothesis, but more research is needed.